Safety and Effectiveness of Muse Cell Transplantation in a Large-Animal Model of Hepatic Fibrosis - Taketo Nishina; Hiroaki Haga; Shohei Wakao; Keita Maki; Kei Mizuno; Tomohiro Katsumi; Kyoko Tomita Hoshikawa; Takafumi Saito; Masahiro Iseki; Michiaki Unno; Mari Dezawa; Yoshiyuki Ueno (Stem Cells International)
Conclusions: Muse cell transplantation was safe and effective in large animal models of hepatic fibrosis. The positive effects were observed in namely 4 weeks after transplantation. Since biochemical as well as histological improvements were demonstrated, future studies including establishing ideal administration protocol seem to be feasible as a preclinical study.